1999
DOI: 10.1152/ajplung.1999.277.5.l881
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces airway epithelial sodium transport in rats

Abstract: Ascent to high altitude leads to pulmonary edema formation in some individuals. Recent laboratory evidence supports the hypothesis that hypoxia may impair the function of the alveolar epithelium and thus augment edema accumulation via reduced clearance of lung liquid. We investigated the effect of hypobaric hypoxia on epithelial sodium transport in adult Sprague-Dawley rats by measuring the nasal transepithelial potential difference (PD) as an index of airway sodium transport. Baseline PDs were similar to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Consistent with this hypothesis, inhibition of the Na-K-ATPase by ouabain decreases nasal PD in the rat [26]. Moreover, in mice, Na-K-ATPase activity represents a potential limiting step in respiratory transepithelial sodium transport [10], and, in the rat, hypoxia decreases nasal PD [26], alveolar fluid clearance and Na-K-ATPase function [27]. However, since ENaC and Na-K-ATPase work in series, one would expect that impairment of Na-K-ATPase function increases intracellular sodium and, in turn, results in a reduced gradient for Na z entry.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with this hypothesis, inhibition of the Na-K-ATPase by ouabain decreases nasal PD in the rat [26]. Moreover, in mice, Na-K-ATPase activity represents a potential limiting step in respiratory transepithelial sodium transport [10], and, in the rat, hypoxia decreases nasal PD [26], alveolar fluid clearance and Na-K-ATPase function [27]. However, since ENaC and Na-K-ATPase work in series, one would expect that impairment of Na-K-ATPase function increases intracellular sodium and, in turn, results in a reduced gradient for Na z entry.…”
Section: Discussionsupporting
confidence: 62%
“…The present authors speculate that in the subjects in this study, the altitude-induced impairment of the transepithelial sodium transport was related to a defect in sodium extrusion. Consistent with this hypothesis, inhibition of the Na-K-ATPase by ouabain decreases nasal PD in the rat [26]. Moreover, in mice, Na-K-ATPase activity represents a potential limiting step in respiratory transepithelial sodium transport [10], and, in the rat, hypoxia decreases nasal PD [26], alveolar fluid clearance and Na-K-ATPase function [27].…”
Section: Discussionmentioning
confidence: 75%
“…While there may be important methodological differences between the present experiments and those using lung cells, the sensitivity to low O 2 that we report here is probably physiologically relevant. One group of investigators (13,51) The second feature of the present experiments is that higher than "normal" levels of O 2 can increase ENaC function. This effect is evident for values up to 40% O 2 ; 95% O 2 did not consistently produce any further increase in Na transport (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Also, an endogenous ouabain-like compound has been found to be increased in high altitude in human plasma (80, 107, 108). One experimental study in rats that reported a reduction in airway epithelial sodium transport from hypoxia supported this hypothesis as well (352).…”
Section: B Hypoxiamentioning
confidence: 86%